Influence of Foreign Language Literature and Culture on Personal Priorities of Students in Kazakhstan - Stanislavovna, Zhumagulova Natalya; Myrzakhmetov, Abay; Lyubov , Аkhriyeva; Vladimirovna, Zhumagulova Yekaterina; Minibulatovna, Mukhamadeyeva Railya; Alkenovna, Мukhamedina Aigul (International Journal of Psychosocial Rehabilitation, 2020)
The present article describes the study of the influence of foreign language literature and culture on the personal priorities of students formed in the process of learning foreign languages. In this context, we understand student youth as students of foreign language specialties of Kazakh universities who study foreign languages and literature. Today, English is the first foreign language in the secondary and higher education system of Kazakhstan. When choosing a second foreign language, preference is given to the German language at school and university. In the context of globalization, foreign languages and foreign language literature do not only interpret foreign language culture, but also contribute to the integration of certain cultural and behavioral attitudes into the native culture of students and their worldview. These attitudes are becoming more attractive to many young people than the values adopted in the national culture.The relevance of the study is due to the attention of Kazakhstani society to the problem of educating young people in the context of globalization and the increasing influence of the so-called Western values on young people.The aim of the research is to study and identify the value priorities of modern Kazakhstani student youth studying English and German at a professional level. The novelty of the study lies in the fact that for the first time the priorities of modern Kazakhstani student youth studying foreign languages, literature and cultures at the professional level were investigated and analyzed. We have identified their main value priorities at the present stage of development of Kazakhstani society and its entry into globalization processes. The article includes the theoretical analysis of the problem of formation of personal priorities in the study of the English language, literature and culture in various communities and conducting a sociological study among students of language specialties of the universityThe study was attended by 149 students of language specialties of two universities, studying foreign languages (English and German) professionally. The study involved students aged 19 to 22 years. The study was conducted from September 2017 to December 2019. The measuring system was developed consisting of four questions and answers to these questions. Each student was to evaluate every answer on a 10-point system.The study identified the following main priorities of students: the desire to be happy and healthy in life, to have a worthy partner for relationships and true family partners, they noted conscience and shame as important moral priorities and the desire to succeed in their profession.The study of the personal priorities of young people in other countries shows that young people also value a good education, a healthy lifestyle, personal relationships, and the possibility of professional ambitions.As a result of the research, it was found that the study of foreign languages, foreign language literature and culture by students of language specialties of the university gives them a high emotional impulse received when reading foreign language literature, forms a single stream of values of domestic, western and world culture, increases their self-esteem, without destroying the foundations of Kazakh identity, passed from generation to generation. However, personal priorities, attitudes and values can change in new generations living in new historical conditions.